PENANAMAN NILAI NILAI PENDIDIKAN AGAMA ISLAM PADA TPQ AL- CHAMIDI SEPANJANG SIDOARJO JAWA TIMUR - Maulidina, Faroh; Mahmud, Amir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the process of instilling Islamic Religious Education (PAI) values at TPQ Al-Chamidi in Sepanjang, Sidoarjo, East Java, as well as its implications for shaping the religious attitudes and behaviors of the students (santri). The research method used is descriptive qualitative, with data collection techniques including observation, in-depth interviews, and documentation. Data analysis is conducted through the stages of data reduction, data presentation, and drawing conclusions descriptively.The results of the study indicate that the instillation of PAI values at TPQ Al-Chamidi is carried out through Qur'an learning activities, habituation of worship practices such as congregational prayers and memorization of daily supplications, exemplary behavior demonstrated by teachers (ustadz and ustadzah), and the cultivation of Islamic morals in daily life. The values instilled include faith, obedience in worship, honesty, discipline, responsibility, and mutual respect.These activities contribute positively to shaping the religious character of the students, such as increasing awareness in worship, politeness, and social concern. In conclusion, the instillation of Islamic Religious Education values at TPQ Al-Chamidi has been effectively implemented and plays an important role in forming the Islamic character of the students. Therefore, it is recommended that TPQ Al-Chamidi continue to develop learning methods and consistently and sustainably reinforce the habituation of PAI values in order to strengthen character building from an early age.